Персоналізований розклад для учнів та викладачів університету - Кошовий, М. Ю. (ХНУРЕ, 2020)
The article reveals the problem of easy access to personalized timetable in university, and proposes a program to solve it. This article is intended for students and teachers in universities with irregular or often changing timetables.